Testing a conceptual model on early opening of the microcirculation in severe sepsis and septic shock: A randomised controlled pilot study. Issue 3 (March 2015) - van der Voort, Peter H.J.; van Zanten, Mark; Bosman, Rob J.; van Stijn, Ilse; Wester, Jos P.J.; van Raalte, Rutger; Oudemans-van Straaten, Heleen M.; Zandstra, Durk F.
Abstract : BACKGROUND: Organ failure in severe sepsis and septic shock may be caused by microcirculatory failure. OBJECTIVE: The objective of this study is to test a conceptual model of microcirculatory failure by using a resuscitation strategy targeting early opening of the constricted microcirculation with active vasodilatation. DESIGN: A randomised controlled pilot study. SETTING: Single-centre mixed medical and surgical tertiary ICU. PATIENTS: Ninety severe sepsis and septic shock patients randomised to early opening microcirculation resuscitation group or standard resuscitation group. INTERVENTIONS: Standard resuscitation group: fluids, noradrenaline, dobutamine and hydrocortisone were given to achieve a mean arterial pressure (MAP) of more than 60 mmHg, cardiac index more than 2.5 l min −1 m −2 and ScvO2 more than 70%. Microcirculation resuscitation group: nitroglycerin, enoximone, dopamine and dexamethasone targeting a microvascular flow index (MFI), measured by sublingual side-stream dark field imaging, more than 2.5. MAIN OUTCOME MEASURE: A decrease in organ failure score (SOFA) on day four of ICU treatment. RESULTS: Data from 37 microcirculation resuscitation and 28 standard resuscitation patients were analysed. In the microcirculation resuscitation group, MFI of more than 2.5 was achieved after a mean ± SD of 7.0 ± 4.6 h. The microcirculation resuscitation group received more fluids, and noradrenaline was equally prescribed in both groups. Per protocol, the decrease in SOFA score at day 4 was not different between groups ( P = 0.64). There was a significant reduction in SOFA score in both groups compared with admission (1.2 and 1.6 in microcirculation resuscitation and standard resuscitation groups, respectively; P = 0.028 and P = 0.045). CONCLUSION: Early opening of the microcirculation in patients with severe sepsis and septic shock using nitroglycerin, enoximone, dopamine and corticosteroids did not result in a faster reduction in organ failure than standard resuscitation. TRIAL REGISTRATION: Clinicaltrials.gov identifier NCT00484133.